1983
DOI: 10.1002/mrd.1120080308
|View full text |Cite
|
Sign up to set email alerts
|

A species‐specific sperm factor dispersing the jelly coat of the egg of the sea urchin, Anthocidaris crassispina

Abstract: A species-specific factor capable of dispersing the jelly coat surrounding eggs has been purified from sperm of the sea urchin, Anthocidaris crassispina. It does not exert its effect on the vitelline layer. The purification has been accomplished by a four-step procedure involving ammonium sulfate fractionation, gel filtration on Sepharose CL-4B, ion-exchange column chromatography on DEAE-cellulose, and affinity column chromatography on heparin-Sepharose CL-6B. The isolated factor is homogenous in sodium dodecy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
1994
1994

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In another ascidian, Ciona intestinalis, belonging to a different family than H. roretzi, only a chymotrypsin-like enzyme is involved in sperm penetration through the egg's vitelline coat (34,41). Trypsin and chymotrypsinlike enzymes have been purified, characterized, and their location demonstrated at the finestructural level in sea urchins (12,28,55,57). Yamada and Aketa (54, 56) and Green and Summers (1 3) have demonstrated that these enzymes promote jelly coat dispersal and lysis of the VE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another ascidian, Ciona intestinalis, belonging to a different family than H. roretzi, only a chymotrypsin-like enzyme is involved in sperm penetration through the egg's vitelline coat (34,41). Trypsin and chymotrypsinlike enzymes have been purified, characterized, and their location demonstrated at the finestructural level in sea urchins (12,28,55,57). Yamada and Aketa (54, 56) and Green and Summers (1 3) have demonstrated that these enzymes promote jelly coat dispersal and lysis of the VE.…”
Section: Discussionmentioning
confidence: 99%
“…Described egg coat lysins can be classified into one of two general categories, enzymatic and stoichiometric. Enzymatic lysins, including acrosin and other trypsin-like and chymotrypsin-like proteases, are reported from mammals (42), anuran amphibians (58), ascidians (23,34), and echinoderms (12,13,28,29,54,55,56,57). Non-enzymatic or stoichiometric lysins are found, to date, in only one group, the molluscs (17, 18,30).…”
Section: Introductionmentioning
confidence: 99%